2011
DOI: 10.4315/0362-028x.jfp-11-230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vanillin, Ethyl Vanillin, and Vanillic Acid on the Growth and Heat Resistance of Cronobacter Species

Abstract: Preservatives could be part of an effective intervention strategy for the control of Cronobacter species in foods, but few compounds with the desired antimicrobial properties have been identified to date. We examined the antibacterial activity of vanillin, ethyl vanillin, and vanillic acid against seven Cronobacter spp. in quarter-strength tryptic soy broth with 5 g/liter yeast extract (TSBYE) adjusted to pH 5.0, 6.0, and 7.0 at 10, 21, and 37°C. All compounds exhibited pH- and temperature-dependant bacterios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…While, the VR of Enterobacter IFVB were higher than the values reported by Li et al () (18 µg ml −1 ) and Citrobacter IFVB showed lower values of VR in comparation with other results (3000 μg ml −1 ) (Harazono et al ). Compared with Yemiş et al (), our results confirmed the resistance to VA on Enterobacter species (8 μg ml −1 ). Also, Harazono et al (), indicated that some Gram‐negative bacteria like Citrobacter are VAR, because they contained AC biosynthetic enzymes (Harazono et al ; Ito et al ).…”
Section: Discussionsupporting
confidence: 85%
“…While, the VR of Enterobacter IFVB were higher than the values reported by Li et al () (18 µg ml −1 ) and Citrobacter IFVB showed lower values of VR in comparation with other results (3000 μg ml −1 ) (Harazono et al ). Compared with Yemiş et al (), our results confirmed the resistance to VA on Enterobacter species (8 μg ml −1 ). Also, Harazono et al (), indicated that some Gram‐negative bacteria like Citrobacter are VAR, because they contained AC biosynthetic enzymes (Harazono et al ; Ito et al ).…”
Section: Discussionsupporting
confidence: 85%
“…Simple phenolic compounds including vanillic acid, ethyl vanillin and vanillin can lessen the heat resistance of C. sakazakii and inhibit growth in reconstituted powdered infant formula. [22] Comparatively little data is available on the antibacterial activity of higher molecular weight polyphenols against the species. Pina-Pérez et al [23] reported that a polyphenol-rich cocoa powder inhibited growth of C. sakazakii in reconstituted infant milk formula stored at 25°C.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al (2010b) have also shown that red muscadine juice can cause a 6-log reduction of C. sakazakii in commercial baby juices in approximately 2 h. Their results suggest that red muscadine could be used to prevent and/or control C. sakazakii in baby food formula. Recently, Yemis et al (2011) investigated the antibacterial activity of vanillin, ethyl vanillin, and vanillic acid as possible preservatives in the intervention strategy for control of Cronobacter spp. They evaluated the effectiveness of the compounds on the growth and heat resistance.…”
Section: Preventive Measuresmentioning
confidence: 99%